2006
DOI: 10.1111/j.1440-1746.2006.04445.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic alterations of the KLF6 gene in hepatocellular carcinoma

Abstract: The results suggest that genetic and epigenetic alteration of KLF6 may play a minor role in the development of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
198
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(207 citation statements)
references
References 15 publications
(31 reference statements)
9
198
0
Order By: Relevance
“…In contrast with the other studies, they only analyzed exon 2. None of the other studies included methods to [10][11][12][13] (ranging between 0 and 15%) and colorectal carcinoma [14][15][16][17][18] (ranging between 0 and 44%). Similar to prostate cancer, the first studies conducted on these other tumors indicated a high frequency of mutation, but this was not reproduced in subsequent reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with the other studies, they only analyzed exon 2. None of the other studies included methods to [10][11][12][13] (ranging between 0 and 15%) and colorectal carcinoma [14][15][16][17][18] (ranging between 0 and 44%). Similar to prostate cancer, the first studies conducted on these other tumors indicated a high frequency of mutation, but this was not reproduced in subsequent reports.…”
Section: Discussionmentioning
confidence: 99%
“…9 The reported frequency of KLF6 mutations in different types of human cancer varies in the different published studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In prostate cancer, four studies have analyzed the frequency of KLF6 mutations. 6,[30][31][32] In the first published study, Narla et al 6 showed a very high frequency, 55%, whereas in the following study, Chen et al 30 obtained a lower frequency, around 15%.…”
mentioning
confidence: 99%
“…17,18 In human HCC, a number of methylation-induced inactivation of genes, such as E-cadherin, p16INK4a, 14-3-3 sigma, SOCS-1 and DLC-1, have already been documented. [19][20][21][22][23][24][25][26][27] However, there is no information on the methylation-mediated silencing of Apo D in HCC. Therefore, we first analyzed the pharmacological induction of Apo D by 5-Azacitidine in human liver cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…DLC1 is a RhoGAP that localizes to focal adhesions specific for RhoA and Cdc42 9,27 , and the GAP activity of DLC1 contributes to its function. In agreement with reported studies, our data indicated that DLC1 significantly suppressed the activation of RhoA and Cdc42, but not Rac1, in stable hepatoma clones of DLC1 (Fig.…”
Section: S549a and S549d Mutants (Supplementary Figs S4 And 5)mentioning
confidence: 99%